Symmetry classes for odd‐order tensors. Issue 5 (5th August 2013) - Olive, M.; Auffray, N.; dell'Isola, Francesco; Forest, Samuel
Abstract We give a complete general answer to the problem, recurrent in continuum mechanics, of determining the number and type of symmetry classes of an odd‐order tensor space. This kind of investigation was initiated for the space of elasticity tensors. Since then, this problem has been solved for other kinds of physics such as photoelectricity, piezoelectricity, flexoelectricity, and strain‐gradient elasticity. In all the aforementioned papers, the results are obtained after some lengthy computations. In a former contribution we provide general theorems that solve the problem for even‐order tensor spaces. In this paper we extend these results to the situation of odd‐order tensor spaces. As an illustration of this method, and for the first time, the symmetry classes of all odd‐order tensors of Mindlin second strain‐gradient elasticity are provided.